Strategi Pembelajaran Aktif dalam Meningkatkan Pemahaman Nilai-Nilai Islam di Sekolah - Nikita Ulia Rahardi; Marhamah Putri; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the implementation of active learning strategies in enhancing the understanding of Islamic values in schools. Active learning provides space for students to actively engage in the learning process, allowing Islamic values to be understood, internalized, and applied in daily life. Through a literature review, this study examines various literatures discussing the concept of active learning, types of active learning strategies, and their impact on students’ understanding and practice of Islamic teachings. The results show that active learning strategies, such as discussions, simulations, religious projects, and reflections, significantly improve students' understanding of Islamic values in a deeper and more contextual manner. Furthermore, the teacher’s role as a facilitator is crucial in creating a conducive learning environment that supports the internalization of Islamic values. This study concludes that active learning not only enhances the cognitive aspects of students but also strengthens their Islamic character.